1999
DOI: 10.1177/000348949910801006
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Function of Guinea Pigs with Experimental Chronic Renal Failure

Abstract: This study aimed to evaluate electrophysiologically the cochlear function of guinea pigs that underwent a five-sixths nephrectomy and, additionally, to explore the synergistic action between chronic renal failure (CRF) and noise. Cochlear potentials were recorded at 1, 2, and 3 months postoperatively. Slight changes in compound action potential and cochlear microphonics were seen at 1 month postoperative, while moderate and profound changes were seen at 2 and 3 months. Endocochlear potential showed no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…A general consensus of animal models was that cochlea is the site of auditory lesion in induced CRF 20. For example, Ohashi et al found that, with greater renal damage, the amplitudes of the cochlear potentials N1 and CM were smaller and latency of N1 was prolonged, but the AP was within normal range 21. Ikeda et al measured the cochlear potentials of guinea pigs with induced renal failure at 1, 2, and 3 months postoperatively 22.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A general consensus of animal models was that cochlea is the site of auditory lesion in induced CRF 20. For example, Ohashi et al found that, with greater renal damage, the amplitudes of the cochlear potentials N1 and CM were smaller and latency of N1 was prolonged, but the AP was within normal range 21. Ikeda et al measured the cochlear potentials of guinea pigs with induced renal failure at 1, 2, and 3 months postoperatively 22.…”
Section: Discussionmentioning
confidence: 99%
“…14,[20][21][22][23][24][25][26] Evidence from induced renal insufficiency in animal studies has constantly reported the correlation between CRF and sensorineural hearing impairment. [20][21][22][23] A general consensus of animal models was that cochlea is the site of auditory lesion in induced CRF. 20 For example, Ohashi et al found that, with greater renal damage, the amplitudes of the cochlear potentials N1 and CM were smaller and latency of N1 was prolonged, but the AP was within normal range.…”
Section: Increased Risk Of Getting Sshl In Patients With Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, chronic kidney disease (CKD) is a well-known risk factor for atherosclerosis, and animal studies [3,4] have reported an association between uremia and cochlear dysfunction. Recently, there are two studies regarding the association between CKD and HL.…”
Section: Introductionmentioning
confidence: 99%
“…Nephrosclerosis, seen occasionally as an incidental finding in aged guinea pigs, is characterized by weakness, anemia, dilute urine, and increased blood urea nitrogen and creatinine (Baggio et al, 1997). In guinea pigs, chronic renal failure may predispose to cochlear dysfunction, especially in the hair cells (Ohashi et al, 1999). This segmental to diffuse interstitial fibrosis causes the kidney to have an irregular surface.…”
Section: A Nephrosclerosismentioning
confidence: 99%